Desempenho de alface crespa cultivadas em sistema convencional e hidropônico - Mazaroski, Pedro Miguel (Universidade Federal de São Carlos, 2024)
Lettuce is the main leafy vegetable in Brazil and worldwide. Its cultivation is mainly done using two planting systems: conventional and hydroponic. However, for most cultivars, there is no clear recommendation on which system is best suited for cultivation. Defining the behavior of these varieties in both cultivation systems can help provide better planting recommendations. The objective was to evaluate and compare the biometric characteristics of different varieties and lines of curly lettuce in a hydroponic system using the Nutrient Film Technique (NFT) and a conventional (field) system, aiming to identify the varieties and lines that adapt best to each system. The evaluation was carried out in a hydroponic system and a conventional system located at the Federal University of São Carlos (UFSCar), Araras. The evaluation was conducted 37 to 40 days after seedling transplantation. The varieties chosen for this experiment were based on lines produced by UFSCar’s genetic improvement program and commercial varieties that are market benchmarks. For the conventional system, the Crocantela, F10 206, and Vanda lines showed the highest fresh aerial mass values, which may be linked to the high plant height and diameter values, as well as earlier bolting compared to the others. In the hydroponic system, these three lines also obtained the top positions for fresh aerial mass, but with less disparity between them. Additionally, the Jade cultivar stood out with the fourth-largest fresh mass, very close to the third-place Vanda. This closeness in values was also observed in the other measured characteristics, due to the more homogeneous nature of the system. The conventional system showed greater variation in results among the lettuces, while the hydroponic system achieved more uniform values. Despite this, the Vanda, Jade, Crocantela, and F10 206 varieties had satisfactory values in both systems.
Performance of curly lettuce grown in conventional and hydroponic systems
Keywords: Lactuca sativa L; NFT; Hortaliça folhosa; Leafy vegetable; Comparação; Comparison; Sistemas de cultivo; Cultivation systems; CIENCIAS AGRARIAS::AGRONOMIA